2023
DOI: 10.1111/bph.16267
|View full text |Cite
|
Sign up to set email alerts
|

From mundane to classic: Sinomenine as a multi‐therapeutic agent

Dan Li,
Zhangfeng Zhong,
Chung‐Nga Ko
et al.

Abstract: Sinomenine (SIN) is an active substance extracted from the traditional Chinese medicine Sinomenium acutum. SIN has been shown to mediate a wide range of pharmacological actions and is known to possess good anti‐inflammatory, immunosuppressive, antitumor, neuroprotective, antiarrhythmic, and other pharmacological effects. Understanding the underlying mechanisms and the association between the targets and the pharmaceutical effects of different diseases is crucial to the discovery and design of new treatment str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 173 publications
0
6
0
Order By: Relevance
“…In addition, sinomenine is therapeutically used as a prognostic indicator [31]. Li et al [32] confirmed that sinomenine inhibited cell proliferation by promoting G1/S cell cycle arrest, enhancing ROS production, and triggering oxidative DNA damage in breast cancer cells [33]. In addition, Li et al found that the MAPK pathway has a role in sinomenine-induced cell death in breast cancer through both ROS-dependent and -independent pathways.…”
Section: Anticancer Role Of Sinomenine In Breast Cancer Proliferationmentioning
confidence: 99%
“…In addition, sinomenine is therapeutically used as a prognostic indicator [31]. Li et al [32] confirmed that sinomenine inhibited cell proliferation by promoting G1/S cell cycle arrest, enhancing ROS production, and triggering oxidative DNA damage in breast cancer cells [33]. In addition, Li et al found that the MAPK pathway has a role in sinomenine-induced cell death in breast cancer through both ROS-dependent and -independent pathways.…”
Section: Anticancer Role Of Sinomenine In Breast Cancer Proliferationmentioning
confidence: 99%
“…Watson. Initially employed for treating rheumatic conditions, this morphinan alkaloid was subsequently found to possess a wide array of pharmacological properties, including notable antioxidant abilities, and is characterized by a low rate of adverse reactions (Li et al, 2023). Further mechanistic investigations have identified that SN's neuroprotective effects predominantly stem from its ability to inhibit oxidative stress, neuroinflammation mediated by Natural alkaloids exert their therapeutic effects in the treatment of epilepsy by agonizing excitatory receptors (A) and agonistically activating inhibitory receptors (B).…”
Section: Antiseizure and Neuroprotective Abilities Of Quinoline Alkal...mentioning
confidence: 99%
“…It induced cell apoptosis (assessed by using annexinV and dead cell kit cell analyzer, Burlington, MA, USA) and autophagy (increased LC3 expression by WB) via inactivation of the signal transducer and activator of transcription 3 activation (STAT3) and by reactive oxygen species (ROS) production [52] Sinomenine or cocculine is an alkaloid found in the root of the climbing plant Sinomenium acutum. It is known to possess anti-inflammatory, immunosuppressive, antitumor, neuroprotective, antiarrhythmic and other pharmacological effects [65]. Sinomenine has been shown to inhibit proliferation of B-CPAP and TPC-1 cells, induce cell apoptosis (as-sessed by Annexin V-FITC and propidium iodide dual staining) and cell cycle arrest (in G2/M phase) [53,54].…”
Section: Alkaloids Effects On Cell Proliferation and Cell Deathmentioning
confidence: 99%